C4, the Pathogenic Determinant of Tomato Leaf Curl Guangdong Virus, May Suppress Post-transcriptional Gene Silencing by Interacting With BAM1 Protein - Li, Zhenggang; Du, Zhenguo; Tang, Yafei; She, Xiaoman; Wang, Xiaomei; Zhu, Yanhua; Yu, Lin; Lan, Guobing; He, Zifu (Frontiers in Microbiology, 2020)
Tomato leaf curl Guangdong virus (ToLCGdV) is a begomovirus associated with a Tomato yellow leaf curl disease (TYLCD) epidemic in Guangdong province, China. Being the least conserved protein among geminivirus proteins, the function of C4 during ToLCGdV infection has not been elucidated. In this study, the infectious clones of ToLCGdV and a ToLCGdV mutant (ToLCGdVmC4) with disrupted C4 ORF were constructed. Although ToLCGdV and ToLCGdVmC4 could infect N. benthamiana and tomato plants, ToLCGdVmC4 elicited much milder symptoms compared with ToLCGdV. To further verify the role of C4 in viral pathogenesis, C4 was expressed in Nicotiana benthamiana from Potato virus X (PVX) vector. The results showed that ToLCGdV C4 enhanced the pathogenicity of PVX and induced more severe developmental abnormalities in plants compared with PVX alone or PVX-mC4. In addition, ToLCGdV C4 suppresses systemic gene silencing in the transgenic N. benthamiana line 16c, but not local gene silencing induced by sense GFP in wild-type N. benthamiana plants. Moreover, C4 suppresses transcriptional gene silencing (TGS) by reducing the DNA methylation level of 35S promoter in 16c-TGS N. benthamiana plants. Furthermore, C4 could also interact with the receptor-like kinase (RLK) BARELY ANY MERISTEM 1 (BAM1), suggesting that C4 may suppress gene silencing by interfering with the function of BAM1 in the cell-to-cell spread of RNAi. All these results suggest that C4 is a pathogenic determinant of ToLCGdV, and C4 may suppress post-transcriptional gene silencing (PTGS) by interacting with BAM1.